Unveiling unconventional ferroelectric switching in multiferroic Ga0.6 Fe1.4O3 thin films through multiscale electron microscopy investigations. (November 2022) - Demchenko, Anna; Homkar, Suvidyakumar; Bouillet, Corinne; Lefèvre, Christophe; Roulland, François; Preziosi, Daniele; Versini, Gilles; Leuvrey, Cédric; Boullay, Philippe; Devaux, Xavier; Viart, Nathalie
Abstract: Understanding the polarization switching mechanisms at play in ferroelectric materials is crucial for their exploitation in electronic devices. The conventional centrosymmetric reference structure-based mechanism which accounts for ferroelectricity in most of the usual displacive ferroelectric materials is too energy-demanding for some newly diagnosed ferroelectric materials such as the Ga2-x Fex O3 (0.8 ≤ x ≤ 1.4) compounds. Some alternative theoretical propositions have been made and need experimental confirmation. A dual-scale electron microscopy study is performed on thin films of the Ga0.6 Fe1.4 O3 multiferroic compound. A wide scale precession-assisted electron diffraction tomography study first allows the determination of the structure the compound adopts in thin films, and even permits the refinement of the atomic positions within this structure. Cationic mobility is suggested for two of the atomic positions through the existence of extra electronic density. A local in situ high resolution scanning transmission electron microscopy study then allows confirming these mobilities by directly spotting the cationic displacements on successively acquired images. The whole study confirms an unconventional switching mechanism via local domain wall motion in this compound. Graphical abstract: Image, graphical abstract